Comparative analysis of the rehabilitation potential of dogs with different types of feeding - V. V. Sydelov (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The long history of interaction between humans and dogs confirms the close relationship between the well-being of both species. Therefore, the development of evaluation criteria for the adaptation of animals in shelters is important for further successful coexistence. The aim of this work was to compare the rehabilitation potential of homeless dogs after a 60-day stay in the shelter against the background of consumption of “premium”, “holistic” and “super premium” rations. The study determined: 11 biochemical indicators, 12 hematological indicators and live weight. Samples were taken three times: for 1 day, 30 and 60 days of stay in the shelter. A significant increase in live weight was established in all 3 groups. At the beginning of the study, 54.5 % of indicators were statistically different between groups, on the 30th day – 45.5 %, at the end of the study such indicators became 81.8 %. A significant decrease in the level of total protein was observed in group No. 1 and a tendency to decrease in the other groups. These changes are associated with a significant decrease in the content of globulins and an increase in albumins in groups № 1 and № 2. An increase in the concentration of creatinine in group № 2 and urea and creatinine in group № 1 was noted. A higher concentration of total calcium and alkaline phosphatase activity was noted in group № 1. The content of total bilirubin significantly decreased in group № 2 and increased in group № 3. The activity of ALT and AST significantly decreased in group № 1 and tended to decrease in other groups. The level of inorganic phosphorus almost did not differ between groups and did not change statistically significantly over time. There was a significant decrease in the total number of leukocytes in groups № 1 and № 2 due to a decrease in the blood concentration of segmented and rod-shaped neutrophils and in group № 2 – monocytes. Similar trends were observed in group № 3. The dynamics of erythrocytopoiesis indicators was marked by a significant increase in hematocrit, the content of erythrocytes and the concentration of hemoglobin in the blood of animals of the first group. Similar trends were observed in other groups. On the 60th day, the above-mentioned parameters and the average volume of erythrocytes did not differ between individual groups. The dynamics of changes in the criteria for assessing the rehabilitation potential during the study allow us to conclude that 60 days are enough to ensure the adaptation of dogs in animal shelters under conditions of regular feeding with balanced rations of a class not lower than “premium”.